Differences in body composition between swimmers and synchronized swimmers - Martinez, M. A.; Hernández, S.; Esteban, P.; Diaz, G.; Labrado, S.; Muñoz, V.; Jimenez, F.; Gonzalez-Rave, J. M. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: From the literature, have been shown that a variety of factors influence in performance exercise. Apart from the physiological parameters, anthropometric parameters, such as body mass, body fat, height, length of limbs, total skinfold have been shown to influence performance in athletes (Maldonado, Mujika and Padilla, 2002). In swimmers, fat mass, upper extremity length and height seem to influence performance (Tuuri, Loftin and Oescher, 2002; Geladas, Nassis and Pavlicevic, 2005; Jagomägi and Jürimäe, 2005). In female swimmers, height, body weight, percent body fat and fat-free weight have an effect on swimming performance (Siders, Lukaski and Bolonchuk, 1993). From the literature haven`t shown this influence in synchronized swimmers. The purpose of this research was to know the differences between female swimmers and synchronized swimmers in body composition. METHODS: 23 female swimmers from Spanish team and 49 female synchronized swimmers participants in Spanish Championship (15,53±0,99 years, 56,12±6,63 kg; 164,28±6,21cm). Body composition was measured by Inbody 230 (Biospace Co., Ltd. Gangnam-gu. Seoul. Korea) the following measurements were taken: body mass, height, BMI, total body water, skeletal muscle mass (SM), percentage body fat (%BF) and body fat (BF). SPSS for Windows 17.0 was used for all statistical, Independent sample T test was used to analyze the differences for each exercises in parametric variables, and Two-Sample Kolmogorov-Smirnov Test in non-parametric variables (body mass). The significant level was p<0.01. RESULTS: The results show significant differences between swimmers and synchronized swimmers in height, total body water, skeletal muscle mass and per centage body fat (p<0.01). Swimmers (168,11±5,36 cm) are significant taller than synchronized swimmers (162,48±5,79 cm). Synchronized swimmers describe low level of total body water (31,24±3,10 kg), SM (23,33±2,56 kg) and %BF (21,3429±5,69) than swimmers (35,80±2,94 kg; 27,20±2,45 kg and 17,84±4,00 respectively). DISCUSSION: It was concluded that significant different exist between female swimmers from two different exercise, synchronized swimming and swimming. So, swimmers require specific anthropometric characteristics different than synchronized swimmers. There seems to be insufficient literature on body composition in both exercises.